The Spread of Droplets and Aerosols of Surgical Motor Handpiece Irrigation Using Different Suction Systems - Tsoi, James K. H.; Ding, Hao; Hon, Ki; Leung, Yiu Yan (Frontiers in Dental Medicine, 2021)
Objective. The present study aimed to compare the effectiveness of various dental suction device combinations in reducing amounts and distance of spread of aerosols and droplets using an electrical surgical motor model with self-irrigation system. Materials and methods. At a standard single-chaired air-conditioned ventilated dental clinic, electrical dental surgical motor with high speed handpiece (Implantmed) cooled with 0.2% fluorescein containing normal saline was used to drill a gypsum block mounted on a phantom head in supine position. A single operator performed thrice for each of the following suction settings: (a) no suction, (b) low volume suction. (c) low volume+high volume suctions, and (d) low volume+external oral suctions. The aerosols (0.1-5.0μm) were measured by a particle counter at the mouth opening of the phantom head, and droplet sizes and distances were analyzed via a machine learning algorithm by identifying the florescence droplets on pre-loaded papers on the floor for each group. Results. Different suctions performed differently from each other in terms of the droplet distance (p=0.007), whereas using settings (c) and (d) can significantly reduced the spread of droplets (41.1±22.9cm and 39.0±18.2cm, respectively) when compared to (a: 58.9±17.1cm). Using settings (c) or (d) can reduce the number for all droplet sizes. The use of (c) was most effective in reducing small aerosol (0.3-1.0μm), while using (d) was most effective in reducing the larger aerosols (3.0-5.0μm). Conclusions. Both external oral suction and high-volume suction were effective in reducing aerosols and droplets generated by the irrigation of surgical motor high speed handpiece.